Pengaruh Pertumbuhan Ekonomi, IPM dan Pengangguran Terhadap Tingkat Kemiskinan di Provinsi Jawa Barat - Ni Nyoman Anggie Dewantari; lucky Rachmawati (Universitas Negeri Surabaya, 2021)
This study aims to see the effect of economic growth, HDI and unemployment onthe poverty rate in West Java province in 2015-2019. Data obtained from theCentral Statistics Agency (BPS) and other sources that support the preparation ofthis research. The method used in this study is to use the panel data method withthe help of Eviews 9 software. Combined data panel between time series data inthe form of time sequences used is 2015-2019 and cross section data, namely in theform of cross-section sequence, namely in the form of 27 districts in West JavaProvince. Based on the results of the analysis, it shows that Economic Growth, HDIand Unemployment partially affect the level of poverty in West Java Province. Keywords: Economic Growth, Human Development Index, Unemployment andPoverty Level